KOMUNIKASI ORGANISASI PENGURUS DALAM PENGEMBANGAN YAYASAN NAURA AZ-ZALFA PANYABUNGAN KABUPATEN MANDAILING NATAL - Elismayanti Rambe (Sekolah Tinggi Agama Islam Taruna Surabaya, 2022)
This study aims to determine the organizational communication that has been carried out by the management in developing the Naura Az-Zalfa Madina Foundation which is located in Panyabungan, Mandailing Natal Regency. The method used in this research is descriptive qualitative. Describe the existing reality as it was found during the author's collection of data in the field. The data collection technique used was interviews with administrators including the chairman of the foundation, school principals and teachers who teach at the foundation. To see the impact on the community, the authors also conducted interviews with the community around where the Foundation is located. The author also made observations regarding the condition of the school's physical buildings and the activities of administrators in communicating. The results of this study indicate that the administrators are able to communicate well with various stakeholders so that the Naura Az-zalfa Foundation continues to exist and develop rapidly with the existence of SDIT which has running first year.